Role of mucilage in seed germination percentage of thirteen medicinal plantsunder different levels of osmotic potential (polyethylene glycol) - تکتم مستشار شهیدی; محمد خواجه حسینی; محمد حسن راشد محصل (علوم و فناوری بذر ایران)
To investigate the role of mucilage in germination of medicinal plants in drought stress conditions, germination test conducted on 4 replications of 25 seeds of 13 species of medicinal plants with mucilage from the families of Lamiaceae, Brassicaceae, Fabaceae, Linaceae and Plantaginaceae in 9 cm diameter petridishes with filter paper premoistined with distilled water in the Seed Laboratory, Faculty of Agriculture, Ferdowsi University of Mashhad in 2012. Different levels of waterpotential (0, -0.1, -0.2, -0.3, -0.4 MPa) using PEG applied and germination percent and mean germination time (MGT) of the species were determined.Results showed osmotic potential levels had a significant effect on the germination percent and mean germination time (MGT) of the species (P≤0.01). P. psylliumM. officinalis and L. usitatissimum were tolerant while, S.officinalis,A.homalocarpum and P.major were sensitive species and other species showed moderate tolerance. It seems amount of the mucilage of species was effective on tolerance of the species. The positive effect of the mucilage on the reduction of stress in the majority of the species may have an ecological benefit in the harsh conditions for the germination of the species with mucilage.